Physical Condition of Indonesian Nusantara League Female Futsal Athletes: A Gender Perspective Review - Windoro, Desrio; Setyawati, Heny; Kristiyanto, Agus; ., Soedjatmiko; Syaputra, Roni; Suganda, Mikkey Anggara (Journal of Ecohumanism, 2025)
Physical ability is an important component in athlete performance, which includes aspects such as strength, speed, agility, and aerobic endurance (VO2max). In the context of futsal, the low understanding and measurement of physical abilities among Liga Nusantara female athletes may hinder the development of their potential. This study aims to measure and analyse the physical abilities of Liga Nusantara female futsal athletes, as well as explore the relationship between these physical variables. The method used was quantitative with a descriptive correlational design, involving 16 athletes taken with a total sampling technique. The instruments used include physical tests which are processed by descriptive analysis. The results showed that the physical condition of the Nusantara League female futsal athletes was generally adequate, there were variations in the ability of strength, speed, agility, and aerobic endurance. The average strength test shows good results, but some athletes are still below average, especially in sit-ups and back-ups. Speed and agility also needed to be improved in some athletes whose results were lower than others, although in general the speed performance was quite good. Aerobic endurance, measured through VO2max, showed good capacity, but inter-athlete differences indicated the need for more intensive cardio training for some individuals. It was concluded that physical ability varies between athletes, with some athletes having strength and endurance that need to be improved. Thus, this study provides valuable insights for designing more effective training programmes to improve the performance of female futsal athletes.